Impact of Promoters on the Catalytic Performance of Nanostructured Nickel/Carbon Matrix for the Decomposition of Methane - Adeel Ahmad; Iqra Reyaz Hamdani; Abdul Rasheed Pillantakath; Ahmed Al Shoaibi; Srinivasakannan Chandrasekar; Mohammad Mozahar Hossain (Advanced Energy & Sustainability Research)
It is of paramount importance to develop efficient catalysts for methane decomposition that withstands high operating temperatures, as the reaction is endothermic equilibrium in nature. Hence, an attempt is made to assess the effect of promoters namely Cu and Mo on the Ni/porous carbon matrix, synthesized using a hydrothermal method. The proportion of Cu and Mo are varied to determine the optimal loading, to maximize conversion and stability using pure methane as the feedstock. The space velocity is varied from 5000 to 8000 mL h−1 gcat to investigate the effects on methane conversion and stability. Both Cu and Mo at 5% loading are found to offer the maximum methane conversion (%) and stability. A conversion exceeding 90% can be achieved at 850 °C with pure methane feed. The catalysts demonstrate remarkable stability up to 4 h, with 40% feed concentration yielding around 83% conversion for Mo and 74% for Cu. The incorporation of promoters had a notable impact on both the catalytic activity and stability as it contributes to the better dispersion of the metal over the catalytic surface, as evidenced by the reduction in the crystallite size. The best performing catalysts exhibit a wide distribution of high‐quality filamentous carbon over their surface.